Psychophysiological assessment of disability in male mice - Mohammadi, Maryam; Karimi, Isaac; Ghashghaii, Ali (Scientific Journal of Zoology, 2014)
Amputation is considered as a defect and its outcome is person’s disability and the incidences of psychological problems. This study examined psychophysiological of disability in male mice with amputed limb. This experimental study was conducted on 30 male mice were randomly divided into 6 groups of 5 animals each: two intact control groups (NC), two groups that their right hands (RH) amputed from elbow joint and two other groups that their right feet (RF) amputed from knee joint. Behavioral tests were performed in each group either after 30 or 60 days after amputation. To investigate the behavior paradigms, we used of forced swimming test for depression, elevated plus maze for anxiety, tail pinch test for stress, Morris water maze for spatial memory and object recognition test for learning. This study demonstrated that the immobility time in FST was RF group on day 30 significant increased compared to NC group on day 60. The open arms entries in EPM were significant decrease in RH and RF groups on days 30 and 60 compared to NC group on day 60. The time in closed arms in EPM was RF group on day 60 significant increased compared to NC group on day 30. RH and RF groups on days 30 and 60 significant increased in this parameter when compared to NC group on day 60. The time in open arms in EPM was significant different in NC group on day 30 as compared to NC group on day 60. RH and RF groups on days 30 and 60 significant decrease compared to NC group on day 60. To sum, limb amputation increased anxious behavior. The trend of working memory in ORT was deteriorated following limb amputation. The response to stress stimulus in TPT was increased post-amputation (P>0.05). The spatial memory in MWM also showed moderate deficit following amputation. Results from present study indicated that amputation can created some psychophysiological disorders. Major reason for which is probably animal’s motor behavior defects, although further studies need to be done on peripheral and central effects of lower sensomotor deprivation while observing ethicl rules.